Peran Pemerintah Desa/Pekon dalam Pencegahan dan Penurunan Stunting Terintegrasi: Tinjauan Siyasah Tanfidziyah - Elvareta Herlambang, Sahda; Frenki; Yasin al Arif, M. (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Stunting is a public health problem that significantly affects the quality of human resources, making its prevention and reduction a shared responsibility of government institutions, including those at the village/pekon level. This study aims to analyze the role of the Village/Pekon Government in integrated stunting prevention and reduction and to examine it from the perspective of Siyasah Tanfidziyah, particularly in relation to the implementation of policies regulated in Pringsewu Regent Regulation Number 10 of 2024. This research employed a qualitative method with a descriptive approach. Data were collected through in-depth interviews, documentation, and literature review involving seven purposively selected informants consisting of village officials and relevant stakeholders directly engaged in stunting programs. The results indicate that the Pekon Government has implemented several strategic programs, including monitoring toddler growth through integrated health posts, providing supplementary food funded by the village budget, implementing the Stunting Foster Father program, and assisting pregnant women experiencing chronic energy deficiency. However, policy implementation still faces challenges such as limited health infrastructure, low public awareness of stunting issues, and inadequate human resources among health cadres. From the perspective of Siyasah Tanfidziyah, the role of the village government reflects the executive function of public service delivery, although strengthening intersectoral coordination and institutional capacity remains necessary.